Sistem Pendukung Keputusan Untuk Menentukan Pelanggan Terbaik Pada Pizza Oei-Oei Medan Menggunakan Metode SAW - Muhammad Yusuf; Hasanul Fahmi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
The management of Pizza Oei-Oei Medan does not yet have a standard system in determining the best customer.m So far, this has been done randomly and without a structure in determining the best customer. Not fair to other customers. It takes a decision support system to determine the best customers who can make decisions from various alternatives and existing criteria in determining the best customers fairly. The method used is SAW (Simple Additive Weighting). SAW is a method that can determine the weight value for each attribute, then proceed with a ranking process that will select the best alternative from a number of alternatives. SAW method can be implemented to find out the best customers based on the criteria and weights that are determined correctly. This research is to determine the best customers at Pizza Oei-Oei Medan. The system is built with Visual Basic Studio programming language with Microsoft Access database.